Successful multiple-dose methotrexate therapy for unruptured repeat ectopic pregnancy with high β-human chorionic gonadotropin value: a case report - Ezeike, Azuka C.; Liman, Idris M.; Babandi, Rukayya M.; Austin-Amadi, Elizabeth O.; Nehemiah, Mfon (International Journal of Research in Medical Sciences, 2024)
Successfully managing an unruptured ectopic pregnancy necessitates prioritizing the preservation of fertility as the primary objective. Medical management is traditionally considered to be more successful at lower ß- human chorionic gonadotropin (HCG) values. However, there is emerging evidence that successful treatment can be achieved with modification of dosage regimen in the presence of high β-HCG value. We reported the successful management of a case of unruptured repeat ectopic pregnancy in a patient with high β-HCG. Mrs PA is a 25-year-old G4P0+3 with previous right salpingectomy due to ruptured ectopic gestation who presented with an ultrasound diagnosis of unruptured left tubal ectopic gestation at a gestational age of 6 weeks. The pre-treatment quantitative β-HCG level was 7066 IU/l. She had multiple dose methotrexate therapy which was well tolerated with normalization of β-HCG levels within 44 days. Hysterosalpingography done six (6) months post-treatment demonstrated patent left fallopian tube. She subsequently had spontaneous conception of an intrauterine pregnancy 16-months post-treatment. The pregnancy was carried to term and culminated in successful delivery at term. Multiple-dose chemotherapy was successful in this patient with high β-HCG level with no reported adverse effect.